Voltage-Gated Ion Channels and the Variability in Information Transfer - Rathour, Rahul Kumar; Kaphzan, Hanoch (Frontiers in Cellular Neuroscience, 2022)
The prerequisites for neurons to function within a circuit and be able to contain and transfer information efficiently and reliably are that they need to be homeostatically stable and fire within a reasonable range, characteristics that are governed, among others, by voltage gated ion channels (VGICs). Nonetheless, neurons entail large variability in the expression levels of VGICs and their corresponding intrinsic properties, but the role of this variability in information transfer is not fully known. In this study we aimed to investigate how this variability of VGICs affects information transfer. For this we used a previously derived population of neuronal model neurons, each with variable expression of five types of VGICs, fast Na+, delayed rectifier K+, A-type K+, T-type Ca++ and HCN channels. These analyses show that the model neurons displayed variability in mutual information transfer, measured as the capability of neurons to successfully encode incoming synaptic information in output firing frequencies. Likewise, variability in expression of VGICs caused variability in EPSPs and IPSPs amplitudes, reflected in variability of output firing frequencies. Finally, using virtual knockout methodology we show that among the ion channels tested A-type K+ channel is the major regulator of information processing and transfer.